Postlockdown performance in french swimming championships - Miguens, N.; Pla, R.; Difernand, A.; Toussaint, J. F.; Sedeaud, A. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To measure the proportion of French swimmers that progressed, stagnated, or regressed during the 2020 national championship compared with previous ones.